The correlation between ferroptosis and m6A methylation in patients with acute kidney injury - Lihua Ni; Rui Bai; Qiuyuan Zhou; Cheng Yuan; Le-Ting Zhou; Xiaoyan Wu (Kidney & Blood Pressure Research, 2022)
Objective: The present research analyzed the correlation between m6A methylation and ferroptosis associated genes (FAGs) in acute kidney injury (AKI) patients. Methods: Bioinformatics analysis of microarray profiles (GSE30718) were performed to select differential expression genes (DEGs). FAGs are derived from systematic analysis of the aberrances and functional implications. The m6A methylation related genes were derived from the molecular characterization and clinical significance of m6A modulators. The multi-gene correlation of ferroptosis and M6A methylation modification were displayed. Then, the CIBERSORT algorithm was used to analyse the proportions of 22 immune cells infiltration. Results: In total, 349 DEGs were extracted between the AKI and control samples, among which 172 genes were up-regulated and 177 were down-regulated. FAGs (SLC1A5, CARS, SAT1, ACSL4, NFE2L2, TFRC and MT1G) and m6A methylation related genes (YTHDF3, WTAP and IGF2BP3) were significantly increased in AKI patients (P< 0.05). FAGs (SAT1, ACSL4 and NFE2L2) was positively correlated with the expression level of m6A methylation genes (P< 0.05). NFE2L2 has high diagnostic value, and level of NFE2L2 was negatively correlated with the degree of follicular helper T (TFH) cells infiltration. Conclusion: Our research could provide a new theoretical basis for the pathogenesis and immune mechanism of AKI.